Awareness of type 2 diabetes mellitus (T2DM) among undergraduate students in School of Health Sciences - Rosdi, Nur Amira Muhamad (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Recently, the incidence of Type 2 Diabetes Mellitus (T2DM) among younger population has been reported to increase (Punthakee et al., 2018). Therefore, a crosssectional study was carried out to identify the level of awareness among this population. A total of 93 undergraduate students at School of Health Sciences USM who fulfilled the inclusion criteria were randomly selected and included in this study. Data was collected using a set of validated and reliable self-administered questionnaires. The data was statistically analysed using the SPSS software version 26. The findings revealed that majority of the respondents had moderate level of awareness on T2DM (89.2%). Most of the respondents had normal BMI level (63.4%). BMI level was found as significantly associated with level of awareness on T2DM (p<0.00). In conclusion, efforts to raise awareness of the risk of diabetes among younger population need to be continued and further enhanced in order to help reduce the number of diabetics among this population in the future.